Im/Politeness in Presidential Trials: A Contrastive Study - Aalaa Yaseen Hassan; Wafaa Mahdi Sahib (Journal of Pragmatics Research, 2026)
This study examines the politeness and impoliteness strategies used by Donald Trump and Saddam Hussein during their respective trials. The judges' questions accusing the presidents were also taken into consideration. The data is drawn from the transcript of Saddam Hussein’s court proceedings, reported by NBC News and MSNBC. The analysis is based on Brown and Levinson’s theory of politeness and Culpeper’s framework of impoliteness. To achieve rigorous qualitative validity, this study utilizes Qualitative Descriptive Analysis to investigate face-work and linguistic aggression within the selected court transcripts. The contrast observed in the study between Trump's and Hussein’s trials can be attributed to several factors, including cultural norms. Trump’s politeness and cooperation reflected the cultural expectations of American society. On the other hand, Hussein’s actions reflected the cultural norms of Iraqi society, where people often prefer a strong, defiant leader. Thus, the two strategies were fundamentally different: both former presidents aimed to project strength, but in opposing ways. The role of the judges also differed. The judge, al-Amiri, managed power dynamics effectively and acknowledged Hussein’s former status, a crucial factor in a political trial. Alternatively, Letitia James primarily conducted an investigative role during Trump’s testimony. Her strategy focused on gathering information rather than asserting authority. In conclusion, the qualitative conclusions are bound by the micro-contextual relationship between speaker intent and participant evaluation within the selected boundaries of the text.